The colour of inequality : ethnicity, class, income, and wealth in Malaysia - Muhammed Abdul Khalid , 1975- (MPH Publishing, 2014)
"This book provides an alternative insight to the debate on inequality in Malaysia, by focusing on the distributionof wealth or assets, rather than income. Despite tremendous increase in national income, the wealth gap in Malaysia is alarmingly high and extremely skewed. For instance, the top 0.2 per cent of depositors in ASB has about 1,133 times more than the bottom 80 per cent of depositors combined. This gap is echoed by the fact that approximately two-thirds of Malaysian workers earn less than RM3,000 per month, and about 90 per cent of Malaysians have nearly zero savings. The current policies are not facilitating improvements in this wealth gap, which could lead to aristocracy where birth, not hard workor talent and effort, matter the most in wealth accumulation. This book explores possible policy interventions that can be undertaken to ensure that economic growth is equitably shared, which is vital for a stable and prosperous society"